Plant evolution and the origin of crop species - Hancock, James F. (CABI, 2004)
This book is arranged in two sections: the first five chapters cover the genetic mechanisms associated with plant evolution (chromosome structure and genetic variability, assortment of genetic variability, the multifactorial genome, polyploidy and gene duplication, and speciation). The second section contains seven chapters which deal with the domestication process and the origin of crop species, with four chapters devoted to the evolution of individual crops (cereals, grain legumes, root crops, and fruits, vegetables and oilseeds). A subject index is supplied. This book is aimed at advanced students and postgraduates.